2013
DOI: 10.1016/j.epsl.2013.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The silicon isotopic composition of the Ganges and its tributaries

Abstract: International audienceThe silicon isotopic composition (δ30Si) of the headwaters of the Ganges River, in the Himalaya, ranged from +0.49±0.01 to +2.17±0.04 at dissolved silicon (DSi) concentrations of 38 to 239μM. Both the concentration and isotopic composition of DSi in the tributaries increased between the highest elevations to where the Ganges leaves the Himlayas at Rishikesh. The tributaries exhibit a linear correlation between δ30Si and DSi that may represent mixing between a low DSi, low δ30Si (e.g., 40μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
(113 reference statements)
4
36
0
Order By: Relevance
“…By isotope mass-balance: (Cockerton et al 2013;Fontorbe et al 2013;Hughes et al 2012). Confirmation of this effect has been demonstrated in both lake dominated boreal regions (Engstrom et al 2010) and in the tropical Congo river (Hughes et al 2012 Mechanisms to induce variations in lake Si retention efficiency 100-1,000 Year timescales Several centennial to millennial scale ontogenetic mechanisms exist to alter lake Si retention efficiency and thereby the magnitude and d 30 Si of river DSi fluxes.…”
Section: Importance Of Lakes For Isotopic Signature Of Landocean Dsi mentioning
confidence: 99%
See 1 more Smart Citation
“…By isotope mass-balance: (Cockerton et al 2013;Fontorbe et al 2013;Hughes et al 2012). Confirmation of this effect has been demonstrated in both lake dominated boreal regions (Engstrom et al 2010) and in the tropical Congo river (Hughes et al 2012 Mechanisms to induce variations in lake Si retention efficiency 100-1,000 Year timescales Several centennial to millennial scale ontogenetic mechanisms exist to alter lake Si retention efficiency and thereby the magnitude and d 30 Si of river DSi fluxes.…”
Section: Importance Of Lakes For Isotopic Signature Of Landocean Dsi mentioning
confidence: 99%
“…The silicon isotopic ratio (d 30 Si) of DSi in rivers is systematically heavier than the ratio in catchment bedrock, since the lighter 28 Si isotope is preferentially incorporated into secondary minerals and BSi , requiring a continental sink to balance river export (Basile-Doelsch et al 2005). d 30 Si of DSi typically (but not always) increases along river longitudinal profiles, implying progressive preferential retention of 28 Si (Hughes et al 2012;Fontorbe et al 2013;Cardinal et al 2010;Cockerton et al 2013). Based on mass-balance De La Rocha et al (2000) concluded that 64 % of weathered silicon is retained in secondary clay minerals, which is in rough agreement with the stoichiometry of weathering reactions.…”
Section: Evidence For Continental Dsi Retention From River Geochemistrymentioning
confidence: 99%
“…It has equally been shown that on average 557 High Himalayan catchments are even more congruent (Fontorbe et al, 2013;558 Kisakürek et al, 2005). This behaviour makes it abundantly clear that dominant 559 secondary mineral formation, and hence isotope fractionation, occurs in the 560 floodplains.…”
Section: Global Implications Of the Ganges LI Chemistry 554mentioning
confidence: 99%
“…Kinetic limitation refers to a situation where the weathering flux (solute, DSi) is operating at maximum capacity for the conditions; increasing the factors that control the weathering rate (essentially temperature or water supply) will increase the rate of DSi export, because there is an excess of fresh material to be weathered. This could be e.g., the high Himalaya, the Andes, or (sub) glacial catchments (Georg et al, 2007;Fontorbe et al, 2013;Opfergelt et al, 2013) where physical erosion greatly outpaces chemical weathering. At very high erosion rates (low weathering intensity or congruency) river δ 30 Si is low: there is no time, and no thermodynamic driving force, for clays to form, soils to develop or biology to have a meaningful influence on the δ 30 Si measured in a stream.…”
Section: Riversmentioning
confidence: 99%
“…Since the first data of DSi in freshwaters by De La Rocha (De La Rocha et al, 2000), δ 30 Si has been analyzed from a number of rivers (and lakes) across the world including the Congo River and tributaries Hughes et al, 2011), the Tana River (Hughes et al, 2012), the Yellow and Yangtze Rivers (Ding et al, 2004(Ding et al, , 2011, the Kalix River in Sweden (Engström et al, 2010), Swiss alpine rivers (Georg et al, 2006), and most recently from the Nile River (Cockerton et al, 2013), the Amazon river and tributaries , areas of central Siberia (Pokrovsky et al, 2013;Panizzo et al, 2017) and the Ganges (Fontorbe et al, 2013;Frings et al, 2015). The range in δ 30 Si from freshwaters, thus far analyzed, now stands at −0.17 to +4.66‰ (Figure 1).…”
Section: Riversmentioning
confidence: 99%